2015
DOI: 10.1097/ta.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Trauma patient readmissions

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…The proportion of pediatric readmissions caused by infection (22.3%) exceeds that reported in the adult literature (1.5–14%). (12, 16, 32) This is not unexpected given that infection, most often respiratory, is the most frequent reason for hospitalization in childhood. (33) Additionally, the subset of children within our cohort who develop neurologic (such as seizures) or neuromuscular chronic conditions as a result of their trauma may be at higher risk of hospitalization and complications from respiratory infections due to impaired airway protective reflexes, restrictive lung disease due to ineffective chest expansion, chronic pulmonary injury due to microaspiration, or lung injury incurred during their injury or during mechanical ventilation post-injury.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The proportion of pediatric readmissions caused by infection (22.3%) exceeds that reported in the adult literature (1.5–14%). (12, 16, 32) This is not unexpected given that infection, most often respiratory, is the most frequent reason for hospitalization in childhood. (33) Additionally, the subset of children within our cohort who develop neurologic (such as seizures) or neuromuscular chronic conditions as a result of their trauma may be at higher risk of hospitalization and complications from respiratory infections due to impaired airway protective reflexes, restrictive lung disease due to ineffective chest expansion, chronic pulmonary injury due to microaspiration, or lung injury incurred during their injury or during mechanical ventilation post-injury.…”
Section: Discussionmentioning
confidence: 94%
“…(1517) Higher injury severity, pre-injury comorbidities, and low socioeconomic status are associated with greater readmission risk in adults. (12, 15, 16, 18, 19) Adult and pediatric trauma differs in regard to mechanism, type of injury, and patient-specific factors. (12, 20, 21) Additionally, care networks and post-discharge resources differ significantly and are likely to influence readmission rates.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies looked at readmissions following traumatic injury in both the general population as well as in the elderly. 4 , 13 , 14 One such study found a readmission rate of 20.6% overall and 26.9% for falls. 14 Focusing only on elderly trauma patients, using statewide data for Washington State, Fawcett et al showed that patients who were 55 years of age and older who survived their initial hospitalization had a readmission rate of 7.9% at 30 days and 25.2% at 1 year.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 13 , 14 One such study found a readmission rate of 20.6% overall and 26.9% for falls. 14 Focusing only on elderly trauma patients, using statewide data for Washington State, Fawcett et al showed that patients who were 55 years of age and older who survived their initial hospitalization had a readmission rate of 7.9% at 30 days and 25.2% at 1 year. 13 Additionally, they showed that the strongest risk factors for readmission were an initial trauma that resulted in severe head injury and discharge to a skilled nursing facility (SNF).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the rate at which trauma patients return to an emergency department (ED) soon after discharge remains high. Prior investigations have identified that up to 14% of injured patients return to an ED within 30 days of their discharge [4][5][6][7][8]. The accuracy of this data is in question, as many patients do not return to the index hospital [5].…”
Section: Introductionmentioning
confidence: 99%